The Effect of Authentic Leadership, Organizational Learning and Technological Innovation on Company Performance With Strategic Management Accounting As An Intervening Variable (Empirical Study on Banking in Banten Province) - Nadya Safira Aprinovita; Imam Abu Hanifah; Fara Fitriyani (Jurnal Riset Akuntansi Terpadu, 2023)
This study aims to examine the effect of Authentic Leadership, Organizational Learning, Technological Innovation on Company Performance with Strategic Management Accounting as an intervening variable. The type of this study was quantitative, data collected by using primary data and questionnaires to obtained the information from the respondents, they were Middle Manager who worked in Main-Branch Office of Banking in Banten Province. The analytical method used Structural Equation Modelling (SEM) with Partial Least Square (PLS) Path Modelling with SmartPLS 3.0 anlysis tools. The result of this study were 1) Authentic Leadership had no effect on Strategic Management Accounting. 2) Organizational Learning had positive and significant effect on Strategic Management Accounting. 3) Technological innovation had positive and significant effect on Strategic Management Accounting. 4) Authentic Leadership had positive and significant effect on Company Performance. 5) Organizational Learning has positive and significant effect on Company Performance. 6) Technological Innovation had positive and significant effect on Company Performance. 7) Strategic Management Accounting had no effect on Company Performance. 8) Authentic Leadership had no effect on Company Performance through Strategic Management Accounting as an intervening variable. 9) Organizational Learning had no effect on Company Performance through Strategic Management Accounting as an intervening variable. 10) Technological Innovation had no effect on Company Performance through Strategic Management Accounting as an intervening variable